Calmodulin kinase II inhibition limits the pro-arrhythmic Ca2+ waves induced by cAMP-phosphodiesterase inhibitors. Issue 1 (4th February 2016) - Bobin, Pierre; Varin, Audrey; Lefebvre, Florence; Fischmeister, Rodolphe; Vandecasteele, Grégoire; Leroy, Jérôme
Abstract: Aims: A major concern of using phosphodiesterase (PDE) inhibitors in heart failure is their potential to increase mortality by inducing arrhythmias. By diminishing cyclic adenosine monophosphate (cAMP) hydrolysis, they promote protein kinase A (PKA) activity under β-adrenergic receptor (β-AR) stimulation, hence enhancing Ca 2+ cycling and contraction. Yet, cAMP also activates CaMKII via PKA or the exchange protein Epac, but it remains unknown whether these pathways are involved in the pro-arrhythmic effect of PDE inhibitors. Methods and results: Excitation–contraction coupling was investigated in isolated adult rat ventricular myocytes loaded with Fura-2 and paced at 1 Hz allowing coincident measurement of intracellular Ca 2+ and sarcomere shortening. The PDE4 inhibitor Ro 20-1724 (Ro) promoted the inotropic effects of the non-selective β-AR agonist isoprenaline (Iso) and also spontaneous diastolic Ca 2+ waves (SCWs). PDE4 inhibition potentiated RyR2 and PLB phosphorylation at specific PKA and CaMKII sites increasing sarcoplasmic reticulum (SR) Ca 2+ load and SR Ca 2+ leak measured in a 0Na + /0Ca 2+ solution ± tetracaine. PKA inhibition suppressed all the effects of Iso ± Ro, whereas CaMKII inhibition prevented SR Ca 2+ leak and diminished SCW incidence without affecting the inotropic effects of Ro. Inhibition of Epac2 but not Epac1 diminished the occurrence of SCWs. PDE3 inhibition with cilostamide induced an SR Ca 2+ leak, which was also blocked by CaMKII inhibition. Conclusion: Our results show that PDE inhibitors exert inotropic effects via PKA but lead to SCWs via both PKA and CaMKII activation partly via Epac2, suggesting the potential use of CaMKII inhibitors as adjuncts to PDE inhibition to limit their pro-arrhythmic effects.